The Future of Geography : How power and politics in space will change our world - Marshall, Tim, ....- (London : Elliott & Thompson Limited, 2023)
Spy satellites orbiting the moon. Space metals worth more than most countries’ GDP. People on Mars within the next ten years. This isn’t science fiction. It’s astropolitics. Humans are heading up and out, and we’re taking our power struggles with us. Soon, what happens in space will shape human history as much the mountains, rivers and seas have on Earth. It’s no coincidence that Russia, China and the USA are leading the way. The next fifty years will change the face of global politics. In this gripping book, bestselling author Tim Marshall lays bare the new geopolitical realities to show how we got here and where we’re going, covering the new space race; great-power rivalry; technology; economics; war; and what it means for all of us down here on Earth. Written with all the insight and wit that have made Marshall the UK’s most popular writer on geopolitics, this is the essential read on power, politics and the future of humanity.
Keywords: Geopolitiek; Internationale politiek